2008
DOI: 10.1021/tx7004212
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Furan Exposure by Metabolic Profiling of Rat Urine with Liquid Chromatography-Tandem Mass Spectrometry and Principal Component Analysis

Abstract: Furan has been found in a number of heated food items and is carcinogenic in the liver of rats and mice. Estimates of human exposure on the basis of concentrations measured in food are not reliable because of the volatility of furan. A biomarker approach is therefore indicated. We searched for metabolites excreted in the urine of male Fischer 344 rats treated by oral gavage with 40 mg of furan per kg of body weight. A control group received the vehicle oil only. Urine collected over two 24-h periods both befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 37 publications
4
92
0
Order By: Relevance
“…NAC-BDA-NAL is a significant metabolite detected in the urine of furan-treated rats (Kellert et al, 2008b;Lu et al, 2009). Data support the hypothesis that this compound is a downstream metabolite of degraded furan-derived protein adducts (Lu et al, 2009;Hamberger et al, 2010).…”
Section: Gates Et Alsupporting
confidence: 60%
See 1 more Smart Citation
“…NAC-BDA-NAL is a significant metabolite detected in the urine of furan-treated rats (Kellert et al, 2008b;Lu et al, 2009). Data support the hypothesis that this compound is a downstream metabolite of degraded furan-derived protein adducts (Lu et al, 2009;Hamberger et al, 2010).…”
Section: Gates Et Alsupporting
confidence: 60%
“…BDA is genotoxic (Marinari et al, 1984;Peterson et al, 2000;Kellert et al, 2008a) and forms adducts with various cellular nucleophiles such as DNA, protein, and polyamines (Chen et al, 1997;Gingipalli and Dedon, 2001;Byrns et al, 2002Byrns et al, , 2004Lu et al, 2009;Peterson et al, 2011), which is evidence that BDA may be responsible for furan-induced toxicities. Conjugates of BDA have been detected in the urine and bile of furan-treated rats (Peterson et al, 2006(Peterson et al, , 2011Kellert et al, 2008b;Lu et al, 2009;Hamberger et al, 2010;Lu and Peterson, 2010).…”
Section: Food and Drug Administration Exploratory Data On Furan In Fmentioning
confidence: 99%
“…A metabolomics study primarily aimed at investigation of a dose-response relationship, Mally et al (2010), established dominantly negative results in terms of metabolic changes in urine although there were some changes in serum concentrations of bile acids at the highest doses A metabolic profiling study, Kellert et al (2008), identified unknown furan metabolites but did not establish strong evidence for biomarker identification…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Kellert et al (2008) describe an explicit metabolomics search for biomarkers of furan exposure in the urine of treated rats. Principle components analysis is used to identify a small number of potential markers from an initial screening involving approximately 450 metabolites (including unknown species).…”
Section: Examples Of Omics Reports Illustrating Components Of Hazard mentioning
confidence: 99%
“…[5][6][7][8] Metabonomics study was divided into four levels, including target analysis, profiling analysis, fingerprint analysis and metabonomics analysis. In this paper, metabonomics study based on the HPLC/MS-ESI-TOF analysis was applied to understanding the metabolic profiling of S100B transgenic mice and identifying the potential biomarkers relating to S100B protein.…”
mentioning
confidence: 99%